Kin-based cultural transmission of tool use in wild chimpanzees - Lamon, Noemie (Sci Adv, 2017)
Current research on animal culture has focused strongly on cataloging the diversity of socially transmitted behaviors and on the social learning mechanisms that sustain their spread. Comparably less is known about the persistence of cultural behavior following innovation in groups of wild animals. We present observational data and a field experiment designed to address this question in a wild chimpanzee community, capitalizing on a novel tool behavior, moss-sponging, which appeared naturally in the community in 2011. We found that, 3 years later, moss-sponging was still present in the individuals that acquired the behavior shortly after its emergence and that it had spread further, to other community members. Our field experiment suggests that this secondary radiation and consolidation of moss-sponging is the result of transmission through matrilines, in contrast to the previously documented association-based spread among the initial cohort. We conclude that the spread of cultural behavior in wild chimpanzees follows a sequential structure of initial proximity-based horizontal transmission followed by kin-based vertical transmission.